Computational investigation of wing-body interaction and its lift enhancement effect in hummingbird forward flight. (7th June 2019) - Wang, Junshi; Ren, Yan; Li, Chengyu; Dong, Haibo
Abstract: A lift enhancement mechanism due to wing-body interaction (WBI) was previously proved to be significant in the forward flight of insect flyers with wide-shape bodies, such as cicada. In order to further explore WBI and its lift enhancement effect in a flapping flight platform with different wing and body shapes, numerical investigations of WBI were performed on the forward flight of a hummingbird in this paper. A high-fidelity computational model of a hummingbird in forward flight was modeled with its geometric complexity. The wing kinematics of flapping flight were prescribed using experimental data from previous literature. An immersed-boundary-method-based incompressible Navier‒Stokes solver was used for the 3D flow simulations of the wing-body system. Analyses on aerodynamic performances and vortex dynamics of three models, including the wing-body (WB), wing-only (WO), and body-only (BO) models, were made to examine the effect of WBI. Results have shown significant overall lift enhancement (OLE) due to WBI. The total lift force of the WB model increased by 29% compared with its WO/BO counterparts. Vortex dynamics results showed formations of unique body vortex pairs on the dorsal thorax of hummingbird where low-pressure zones were created to generate more body lift. Significant interactions between body vortex and leading-edge vortex (LEV) were observed, resulting in strengthened LEVs near the wing root and enhanced wing lift generation during downstroke. Parametric studies showed strong OLEs over wide ranges of body angle and advance ratio, respectively. The contribution of OLE from the hummingbird body increased with increasing body angle, and the wing pair's contribution increased as advance ratio increased. Results from this paper supported that lift enhancement due to WBI is potentially a general mechanism adopted by different kinds of flapping-wing flyers, and demonstrated the potential of WBI in the design of flapping-wing micro aerial vehicle (MAV) that pursue higher performance.